PENURUNAN KADAR GULA DARAH DAN LINGKAR PERUT PENDERITA DIABETES MELITUS TIPE-2 MENGGUNAKAN YOGURT KECAMBAH KACANG TOLO (Vigna unguiculata) - Winarsi, Hery; Ramadhan, Gumintang Ratna; Dewi, Intan Anggita; Hernayanti, Hernayanti (Program Studi Ilmu Gizi, Jurusan Kesmas Fakultas Ilmu-Ilmu Kesehatan Universitas Jenderal Soedirman, 2022)
This study aims to determine the effect of giving Cowpea bean sprouts yogurt (CowpeaS-Yo) on blood glucose levels and abdominal circumference of patients with type-2 diabetes mellitus (T2DM). This experimental study used a pretest-posttest control group design, with 18 female subjects with T2DM, randomly divided into 2 groups, 9 people each. Group I was given CowpeaS-Yo, while group II was given a placebo as a control, 200 ml/day, for 2 months. Before and after 2 months of intervention, the subjects were measured for their abdominal circumference, and 1 mL of their blood sample was taken, to be checked for blood glucose levels. Data were analyzed using paired sample t-test. After two months of intervention, blood sugar levels decreased significantly from 259.33 mg/dl to 231.78 mg/dl (P=0.013) in the group consuming CowpeaS-Yo, as well as abdominal circumference decreased from 95.00 cm to 91 cm. .67 cm (P=0.008), compared to the control group. In conclusion, yocamcalo consumption was able to prevent the development of T2DM with central obesity, by reducing fasting blood glucose levels and abdominal circumference of patients.